Flame-retardant salt-corrosion-resistant protective film for ship floor
By applying wear-resistant layers and base film layers made of materials such as ethylene-acrylic copolymer and glassy ceramic flame retardant powder on PVC floors, combined with UV coating and additives, the problem of corrosion of PVC floors in the offshore environment is solved, and the waterproof, salt spray resistance and flame retardant performance of the floor is improved, and the service life is extended.
Patent Information
- Application Number
- CN202411990511.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-22
AI Technical Summary
PVC floors are exposed to salt spray for a long time in the offshore environment, which is prone to corrosion, resulting in surface loss, discoloration, reduced hardness and easy damage, and shortened service life.
Wear-resistant and bottom film layers made of ethylene-acrylic copolymer, glassy ceramic flame retardant powder, plasticizer, antioxidant, inner lubricant and outer lubricant are used, combined with UV coating and additives to form protective films to improve the waterproof, salt spray resistance and flame retardant properties of the floor.
It significantly improves the waterproof and salt spray corrosion resistance of the floor, prevents whitening, discoloration and cracking, extends service life, and provides flame retardant and alkyl-resistant effects in offshore environments.
Smart Images

Figure CN119858370A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flooring, in particular to a protective film for a flame-retardant and salt-corrosion-resistant ship floor. Background Art
[0002] When PVC floor is installed on ocean-going ships, the floor is in a salt spray environment for a long time. The salt in the salt spray may corrode the surface of the PVC floor, making the floor surface lose its luster. In addition, the salt spray may cause the floor to change color, appear white or fade, and affect the appearance.
[0003] Secondly, the chemical components in the salt spray will gradually corrode the PVC floor, causing its physical properties to deteriorate. The hardness of the floor may decrease, making it more susceptible to scratches or wear. At the same time, its toughness will also be damaged, making it prone to cracks or breaks, thus shortening the service life of the PVC floor. Summary of the invention
[0004] Purpose of the invention: The technical problem to be solved by the present invention is to provide a flame-retardant and salt-corrosion-resistant protective film for ship floors, which solves the problem that the life of PVC floors will be shortened due to salt spray corrosion during long-term sailing at sea.
[0005] Technical Solution
[0006] To solve the above problems, the technical solution provided by the present invention is:
[0007] A flame retardant and salt corrosion resistant ship floor protective film comprises a wear-resistant layer or a bottom film layer, wherein the wear-resistant layer and the bottom film layer are prepared from ethylene-acrylic acid copolymer, glassy ceramic flame retardant powder, plasticizer, antioxidant, internal lubricant and external lubricant.
[0008] Furthermore, the ethylene-acrylic acid copolymer is ethylene-acrylic acid copolymer resin particles.
[0009] Furthermore, the acrylic acid content in the ethylene-acrylic acid copolymer is 7%-10%.
[0010] Furthermore, the glassy ceramic flame retardant powder accounts for 10%-15% of the ethylene-acrylic acid copolymer particles.
[0011] Furthermore, the antioxidant is 0.2%-0.3%.
[0012] Furthermore, the plasticizer is dioctyl terephthalate, the antioxidant is hindered phenol or phosphite, the internal lubricant is stearic acid, and the external lubricant is PE wax or paraffin.
[0013] Furthermore, the ethylene-acrylic acid copolymer is 100 parts by mass, the glassy ceramic flame retardant powder is 13 parts by mass, the plasticizer is 20 parts by mass, the antioxidant is 0.2 parts by mass, the internal lubricant is 1 part by mass, and the external lubricant is 0.7 parts by mass.
[0014] Furthermore, the wear-resistant layer is coated with a UV coating, and an additive is added to the UV coating.
[0015] Furthermore, the auxiliary agents are silane coupling agents and hindered amine light stabilizers.
[0016] Furthermore, the silane coupling agent is 2%-5% and the hindered amine light stabilizer is 0.1%-0.5%.
[0017] Beneficial Effects
[0018] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0019] The technical solution provided by the present invention can improve the waterproof and salt spray corrosion resistance by compounding ethylene-acrylic acid copolymer film on the surface and bottom layer of the floor, and extrude the ethylene-acrylic acid copolymer into a wear-resistant layer and a bottom film after adding glassy ceramic flame retardant powder to the ethylene-acrylic acid copolymer and mixing them evenly, and then heat-pressing the ethylene-acrylic acid copolymer with the middle and bottom materials of the floor to prevent the floor from turning white, changing color, and cracking; secondly, adding an auxiliary agent to the UV layer to produce a hydrophobic effect so that seawater is not easy to stay on the surface of the floor, preventing seawater from corroding the surface, and also increasing its anti-aging performance. Thus, the floor can achieve the effect of flame retardancy and salt spray resistance to adapt to the marine environment. The prepared floor can be used as a ship floor, and while having flame retardancy and smoke suppression capabilities, it has excellent salt spray resistance and weather resistance, can adapt to the marine environment, and enhances its service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a product structure diagram of Embodiment 1 of the present invention;
[0021] Figure 2 This is a production process flow chart of Example 1 of the present invention. DETAILED DESCRIPTION
[0022] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0023] Example 1
[0024] Combined with Figure 1-2 , a flame retardant and salt corrosion resistant protective film for ship floors. By improving the wear-resistant layer and bottom film layer of conventional floors, the floors have higher flame retardancy, waterproof and salt spray resistance, and anti-aging effects, so that the floors can be used for a long time in the marine environment.
[0025] The wear-resistant layer and base film layer of the floor are made of ethylene-acrylic acid copolymer and glassy ceramic flame-retardant powder, which are mixed evenly and then extruded. In order to further increase the hydrophobicity and anti-aging functions of the floor, conventional floors will be coated with a UV layer on the wear-resistant layer. In order to enhance the hydrophobicity and anti-aging properties of the floor in the marine environment, when coating the UV layer on the wear-resistant layer, additives can also be added to the UV layer, thereby further increasing the flame retardant and salt spray resistant effects of the floor to adapt to the marine environment.
[0026] The wear-resistant layer and bottom film layer of the floor are located on the surface and bottom layer of the conventional floor. The existing floor panels can be made to have stronger flame retardant, waterproof, salt spray resistant and anti-aging properties by changing the materials of the wear-resistant layer and the bottom film layer.
[0027] The wear-resistant layer and the bottom film layer are formed by adding ethylene-acrylic acid copolymer particles and glassy ceramic flame retardant powder to the mixture and then extruding it. The ethylene-acrylic acid copolymer film has excellent waterproof performance and good salt spray resistance. The composite ethylene-acrylic acid copolymer film on the surface and bottom layers of the floor can effectively isolate salt water to prevent it from corroding the floor.
[0028] The ethylene-acrylic acid copolymer particles are selected from ethylene-acrylic acid copolymer particles with an acrylic acid content of 7%-10%. The high ethylene content in the ethylene-acrylic acid copolymer particles can increase the flexibility of the ethylene-acrylic acid copolymer particles, make the ethylene-acrylic acid copolymer particles have better processing performance, and are not easy to break; the polar groups in acrylic acid have a great effect on enhancing salt spray resistance and can increase impact resistance, but too high a content will make the material hard and brittle, narrow the processing temperature range, and increase the processing difficulty.
[0029] There are polar groups such as hydroxyl groups on the molecular chain of ethylene-acrylic acid copolymer, which has low adsorption to salt ions. At the same time, a hydrogen bond network is formed to limit the movement of the molecular chain and reduce the diffusion rate of salt spray. The hydrogen bonds and hydroxyl groups of ethylene-acrylic acid copolymer can inhibit the crystallization of ethylene-acrylic acid copolymer, and the amorphous area will increase, which can accommodate and disperse salt ions, reduce aggregation on the surface and inside of the material, and enhance salt spray resistance. Ethylene-acrylic acid copolymer also has good barrier properties, which can prevent moisture and corrosive media from penetrating into the interior of the material.
[0030] In the wear-resistant layer and bottom film layer formed by adding glassy ceramic flame retardant powder to ethylene-acrylic acid copolymer particles, the glassy ceramic flame retardant powder accounts for 10%-15% of the ethylene-acrylic acid copolymer particles, that is, the ratio of ethylene-acrylic acid copolymer particles to glassy ceramic flame retardant powder is 10:1-1.5. If the amount of glassy ceramic flame retardant powder added is too little, the flame retardant effect of the wear-resistant layer and the bottom film layer will not be achieved. If the amount of glassy ceramic flame retardant powder added is too much, the transparency of the wear-resistant layer and the bottom film layer will be reduced too much, which will reduce the visual effect of the floor and affect the appearance.
[0031] The wear-resistant layer and base film layer formed by the glassy ceramic flame-retardant powder can be flame-retardant in three aspects: first, the physical barrier effect. When the flame-retardant powder encounters flames, it will gather and melt on the surface to form a physical barrier layer; second, the heat absorption and cooling effect. The flame-retardant powder has a high specific heat capacity and can absorb a large amount of heat when heated; third, the effect of diluting combustible gases. The flame-retardant powder will release non-combustible gases such as carbon dioxide during the thermal reaction.
[0032] In the process of making the wear-resistant layer and the base film layer, in addition to ethylene-acrylic acid copolymer particles and glassy ceramic flame retardant powder as the main materials, other additives are also required, including plasticizers, antioxidants, internal lubricants, and external lubricants.
[0033] Plasticizers, antioxidants, internal lubricants and external lubricants are essential materials for the production of conventional floors. The wear-resistant layer and base film layer having ethylene-acrylic acid copolymer particles and glassy ceramic flame retardant powder can directly use the plasticizers, antioxidants, internal lubricants and external lubricants used in conventional floors on the market.
[0034] The amount of antioxidant added is 0.2%-0.3%. Adding too much will lead to a decrease in mechanical properties and a higher cost; adding too little will reduce its anti-aging ability.
[0035] On conventional floors, after the surface layer and the bottom layer are replaced with a wear-resistant layer and a base film layer formed by a mixture of ethylene-acrylic acid copolymer particles and glassy ceramic flame retardant powder, a layer of UV coating can be applied on the wear-resistant layer. The UV coating has additives added to the conventional UV coating, and the additives include silane coupling agents and hindered amine light stabilizers.
[0036] The UV coating is preferably added with 2%-5% of a silane coupling agent and 0.1%-0.5% of a hindered amine light stabilizer.
[0037] When the amount of silane coupling agent added is about 2%-5%, it has a hydrophobic effect and has little effect on transparency. It can also form a stable chemical bond, enhance the bonding strength with the base material, and will not cause problems such as agglomeration due to excessive addition. When the amount of hindered amine light stabilizer added is 0.1%-0.5%, it can better absorb ultraviolet rays and prevent material aging, and at the same time, it has little effect on transparency.
[0038] Excessive amounts of silane coupling agents and hindered amine light stabilizers will lead to reduced transparency of the UV coating, while too little silane coupling agents and hindered amine light stabilizers will lead to insufficient functionality. 2%-5% silane coupling agents and 0.1%-0.5% hindered amine light stabilizers are relatively balanced contents.
[0039] Adding silane coupling agent can achieve a hydrophobic effect, making it difficult for seawater to stay on the surface and reducing corrosion to the material.
[0040] Adding hindered amine light stabilizers can increase the anti-aging function. First, when the UV coating is exposed to ultraviolet rays, the chemical bonds in the coating will be destroyed and free radicals will be generated. Hindered amine light stabilizers can capture these free radicals to produce nitroxide free radicals. Second, during the photooxidation process, peroxides will be generated in the coating. Hindered amine light stabilizers can react with peroxides and decompose them. Third, an important feature of hindered amine light stabilizers is that they have a regeneration function. During the reaction, nitroxyl free radicals can react with hydrogen donors in the coating to regenerate nitroxide free radicals. This regeneration mechanism allows the hindered amine light stabilizer to continue to play a stabilizing role. As long as there are enough hydrogen donors in the coating, it can continuously participate in the process of capturing free radicals and decomposing peroxides, effectively delaying the aging of the coating.
[0041] The specific implementation steps are:
[0042] (1) Weigh the corresponding weight portions of the raw materials, 100 parts of ethylene-acrylic acid copolymer resin (acrylic acid content is 7%-10%), 10-15 parts of glassy ceramic flame retardant powder, 10-20 parts of plasticizer, 0.2-0.3 parts of antioxidant, internal lubricant stearic acid, and 0.5-1 parts of external lubricant,
[0043] Among them, the plasticizer is preferably dioctyl terephthalate, the antioxidant is preferably hindered phenols or phosphites, the internal lubricant is preferably stearic acid, and the external lubricant is preferably PE wax, paraffin, etc.
[0044] Add the above materials to a high-speed mixer after mixing, raise the temperature to 80-100°C, rotate at 50-150 r / min, and mix and stir evenly;
[0045] (2) When the temperature of the high-mix material reaches 80-100, the cold mix is started, and the material in the high-speed mixer is unloaded to the cold mix. When the temperature of the material drops to 50°C, the material in the cold mix is unloaded into the storage tank for standby use;
[0046] (3) feeding the mixed material into a twin-screw extruder for melt blending, controlling the extrusion barrel temperature at 200-230° C., and extruding through a die to form a wear-resistant layer;
[0047] (4) hot pressing the extruded ethylene-acrylic acid copolymer wear-resistant layer, middle material, bottom material, and ethylene-acrylic acid copolymer bottom film layer at a temperature of 130-150° C. and a pressure of 3-10 MPa, which can be adjusted according to the thickness of the material;
[0048] Among them, the middle material and the base material can be made according to panels with different needs. There is no limitation on the middle material and the base material. The surface and bottom layers of any floor can be replaced with the prepared ethylene-acrylic acid copolymer wear-resistant layer and the ethylene-acrylic acid copolymer bottom film layer, thereby achieving a higher flame retardant and salt spray resistant effect to adapt to the marine environment.
[0049] (5) UV coating: select a UV paint with good wear resistance, add 2%-5% of silane coupling agent and 0.1%-0.5% of hindered amine light stabilizer, and perform UV coating on the product obtained in step (4);
[0050] (6) Punching: Punching the floor into corresponding specifications;
[0051] (7) Chamfering and edge cutting.
[0052] (8) Packaging.
[0053] The proportion of raw materials is specifically selected as follows:
[0054] 100 parts by mass of ethylene-acrylic acid copolymer, 13 parts by mass of glassy ceramic flame retardant powder, 20 parts by mass of plasticizer, 0.2 parts by mass of antioxidant, 1 part by mass of internal lubricant and 0.7 parts by mass of external lubricant are used to produce wear-resistant layer or base film layer samples, which are used as experimental examples for comparison with conventional floors in a salt spray marine environment.
[0055] A polyvinyl chloride wear-resistant layer, which is a wear-resistant layer or a bottom film layer of a conventional floor, was selected as a comparative example, so as to conduct a comparative experiment between the experimental example and the comparative example.
[0056] Ethylene-acrylic acid copolymer wear layer formula:
[0057] Ethylene-acrylic acid copolymer Glassy ceramic flame retardant powder Plasticizers Antioxidants Internal lubricant External lubricant 100 13 20 0.2 1 0.7
[0058] Test method: The experiment selected neutral salt spray test.
[0059] Neutral salt spray test: dissolve chemically pure sodium chloride in distilled water to prepare a 5% ± 0.1% salt solution with a pH value between 6.5 and 7.2. The test chamber atomizes the salt solution to simulate the marine environment of salt spray. The test specimen is placed at an angle of 15-30° to the vertical plane so that the specimen is continuously exposed to the salt spray. The test cycle is 168 hours. After the test, it is naturally dried indoors for 30 minutes, and then the residual salt spray is gently washed off with clean water, and the appearance of the specimen is observed.
[0060] The following table shows the recorded data of the neutral salt spray test comparison between the polyvinyl chloride wear layer and the ethylene-acrylic acid wear layer.
[0061]
[0062] It can be seen from the experimental records of the above-mentioned neutral salt spray test that the wear-resistant layer and the base film layer formed by mixing ethylene-acrylic acid copolymer particles and adding glassy ceramic flame retardant powder and then extruding have obvious corrosion resistance and aging resistance compared with the wear-resistant layer and base film layer of conventional floors. Ethylene-acrylic acid copolymer particles adding glassy ceramic flame retardant powder can improve the waterproofness and salt spray corrosion resistance of the wear-resistant layer or the base film layer, prevent it from whitening, discoloration, and cracking, thereby improving the waterproofness and salt spray corrosion resistance of the floor.
[0063] In actual production:
[0064] The UV layer is wear-resistant, hydrophobic and anti-aging.
[0065] The ethylene-acrylic acid wear-resistant layer has flame retardant, waterproof, salt spray resistant and aging resistance effects.
[0066] The vinyl acrylic base membrane prevents salt water from eroding the floor from below.
[0067] The middle material, base material and color film can be replaced with other floor materials.
[0068] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A flame retardant and salt corrosion resistant protective film for ship floors, characterized in that: It comprises a wear-resistant layer or a bottom film layer, wherein the wear-resistant layer and the bottom film layer are prepared from ethylene-acrylic acid copolymer, glassy ceramic flame retardant powder, plasticizer, antioxidant, internal lubricant and external lubricant.
2. The flame retardant and salt corrosion resistant ship floor protective film according to claim 1, characterized in that: The ethylene-acrylic acid copolymer is ethylene-acrylic acid copolymer resin particles.
3. The flame retardant and salt corrosion resistant ship floor protective film according to claim 1, characterized in that: The acrylic acid content in the ethylene-acrylic acid copolymer is 7%-10%.
4. The flame retardant and salt corrosion resistant ship floor protective film according to claim 1, characterized in that: The glassy ceramic flame retardant powder accounts for 10%-15% of the ethylene-acrylic acid copolymer particles.
5. The flame retardant and salt corrosion resistant ship floor protective film according to claim 1, characterized in that: The antioxidant is 0.2%-0.3%.
6. The flame retardant and salt corrosion resistant ship floor protective film according to claim 1, characterized in that: The plasticizer is dioctyl terephthalate, the antioxidant is hindered phenols or phosphites, the internal lubricant is stearic acid, and the external lubricant is PE wax or paraffin.
7. The flame retardant and salt corrosion resistant ship floor protective film according to claim 1, characterized in that: The ethylene-acrylic acid copolymer comprises 100 parts by mass, the glassy ceramic flame retardant powder comprises 13 parts by mass, the plasticizer comprises 20 parts by mass, the antioxidant comprises 0.2 parts by mass, the internal lubricant comprises 1 part by mass, and the external lubricant comprises 0.7 parts by mass.
8. The flame retardant and salt corrosion resistant ship floor protective film according to claim 1, characterized in that: The wear-resistant layer is coated with a UV coating, and an auxiliary agent is added into the UV coating.
9. The flame retardant and salt corrosion resistant ship floor protective film according to claim 8, characterized in that: The auxiliary agents are silane coupling agent and hindered amine light stabilizer.
10. The flame retardant and salt corrosion resistant ship floor protective film according to claim 9, characterized in that: The silane coupling agent is 2%-5% and the hindered amine light stabilizer is 0.1%-0.5%.
Citation Information
Patent Citations
Bio-based extruded LVT floor, formula and preparation method of bio-based extruded LVT floor
CN117569535A
Plastic floor for ship and processing method
CN118306090A
Salt-mist-resistant packaging adhesive film, preparation method thereof and photovoltaic module
CN119119900A